Effect of preoperative pelvic floor muscle training on pelvic floor muscle contraction and symptomatic and anatomical pelvic organ prolapse after surgery: randomized controlled trial. (9th June 2020) - Nyhus, M. Ø.; Mathew, S.; Salvesen, Ø.; Salvesen, K. Å.; Stafne, S.; Volløyhaug, I.
ABSTRACT: Objectives: To evaluate the effect of preoperative pelvic floor muscle training (PFMT) on pelvic floor muscle (PFM) contraction, symptoms of pelvic organ prolapse (POP) and anatomical POP, 6 months after prolapse surgery, and to assess the overall changes in PFM contraction, POP symptoms and pelvic organ descent after surgery. Methods: This was a randomized controlled trial of 159 women with symptomatic POP, Stage 2 or higher, scheduled for surgery. Participants were randomized to intervention including daily PFMT from inclusion to surgery ( n  = 81) or no intervention (controls; n  = 78). Participants were examined at inclusion, on the day of surgery and 6 months after surgery. PFM contraction was assessed by: vaginal palpation using the Modified Oxford scale (MOS; 0–5); transperineal ultrasound, measuring the percentage change in levator hiatal anteroposterior diameter (APD) from rest to maximum PFM contraction; vaginal manometry; and surface electromyography (EMG). POP distance from the hymen in the compartment with the most dominant prolapse and organ descent in the anterior, central and posterior compartments were measured on maximum Valsalva maneuver. POP symptoms were assessed based on the sensation of vaginal bulge, which was graded using a visual analog scale (VAS; 0–100 mm). Linear mixed models were used to assess the effect of PFMT on outcome variables. Results: Of the 159 women randomized, 151 completed the study, comprising 75 in the intervention and 76 in the control group. Mean waiting time for surgery was 22 ± 9.7 weeks and follow‐up was performed on average 28 ± 7.8 weeks after surgery. Postoperatively, no difference was found between the intervention and control groups with respect to PFM contraction assessed by vaginal palpation (MOS, 2.4 vs 2.2; P  = 0.101), manometry (19.4 vs 19.7 cmH2 O; P  = 0.793), surface EMG (33.5 vs 33.1 mV; P  = 0.815) and ultrasound (change in hiatal APD, 20.9% vs 19.3%; P  = 0.211). Furthermore, no difference between groups was found for sensation of vaginal bulge (VAS, 7.4 vs 6.0 mm; P  = 0.598), POP distance from the hymen in the dominant prolapse compartment (−1.8 vs −2.0 cm; P  = 0.556) and sonographic descent of the bladder (0.5 vs 0.8 cm; P  = 0.058), cervix (−1.3 vs −1.1 cm; P  = 0.569) and rectal ampulla (0.3 vs 0.4 cm; P  = 0.434) . In all patients, compared with findings at initial examination, muscle contraction improved after surgery, as assessed by palpation (MOS, 2.1 vs 2.3; P  = 0.007) and ultrasound (change in hiatal APD, 17.5% vs 20.1%; P  = 0.001), and sensation of vaginal bulge was reduced (VAS, 57.6 vs 6.7 mm; P  < 0.001). In addition, compared with the baseline examination, POP distance from the hymen in the dominant prolapse compartment (1.9 vs −1.9 cm; P  < 0.001) and sonographic descent of the bladder (1.3 vs 0.6 cm; P  < 0.001), cervix (0.0 vs −1.2 cm; P  < 0.001) and rectal ampulla (0.9 vs 0.4 cm; P  = 0.001) were reduced . Conclusions: We found no effect of preoperative PFMT on PFM contraction, POP symptoms or anatomical prolapse after surgery. In all patients, PFM contraction and POP symptoms were improved at the 6‐month follow‐up, most likely due to the anatomical correction of POP. Copyright © 2020 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. This article includes Author Insights, a video abstract available at https://www.isuog.org/resource/uog-video-abstract-preoperative-pelvic-floor-muscle-training-pelvic-floor-muscle-contraction.html RESUMEN: Efecto de los ejercicios preoperatorios de los músculos del suelo pélvico en la contracción de los músculos del suelo pélvico y en el prolapso sintomático y anatómico de los órganos pélvicos después de la cirugía: ensayo controlado aleatorizado Objetivos: Evaluar el efecto de los ejercicios preoperatorios para los músculos del suelo pélvico (EMSP) en la contracción de los músculos del suelo pélvico (MSP), los síntomas del prolapso de órganos pélvicos (POP) y el POP anatómico, seis meses después de la cirugía de prolapso, y evaluar los cambios generales en la contracción de los MSP, los síntomas del POP y el descenso de los órganos pélvicos después de la cirugía. Métodos: Este fue un ensayo controlado aleatorizado de 159 mujeres con POP sintomático, en Etapa 2 o superior, y en lista de espera para cirugía. Las participantes se asignaron al azar a una intervención que incluía EMSP diarios desde el ingreso hasta la cirugía (n=81) o ninguna intervención (controles; n=78). Las participantes fueron examinadas en el momento de su ingreso, el día de la cirugía y 6 meses después de la cirugía. La contracción de los MSP se evaluó mediante: palpación vaginal mediante la escala Oxford modificada (EOM; 0‐5); ecografía transperineal, medición del porcentaje de cambio en el diámetro anteroposterior (DAP) del levador hiatal desde el reposo hasta la máxima contracción de los MSP; manometría vaginal; y electromiografía (EMG) de superficie. Se midió la distancia del POP desde el himen en el compartimento con el prolapso más dominante y el descenso de los órganos en los compartimentos anterior, central y posterior en la maniobra de Valsalva máxima. Los síntomas del POP fueron evaluados en base a la sensación de abultamiento vaginal, la cual fue calificada usando una escala análoga visual (EAV; 0–100 mm). Se utilizaron modelos mixtos lineales para evaluar el efecto de los EMSP en las variables de resultado. Resultados: De las 159 mujeres asignadas al azar, 151 completaron el estudio, de las cuales 75 eran el grupo bajo intervención y 76 el grupo de control. El tiempo medio de espera para la cirugía fue de 22±9, 7 semanas y el seguimiento se realizó en promedio a las 28±7, 8 semanas después de la cirugía. En el postoperatorio, no se encontraron diferencias entre los grupos de intervención y de control con respecto a la contracción de los MSP evaluada mediante palpación vaginal (EOM, 2, 4 vs 2, 2; P=0, 101), manometría (19, 4 vs 19, 7cm H2O; P=0, 793), EMG de superficie (33, 5 vs 33, 1 mV; P=0, 815) y ecografía (cambio en DAP del hiato, 20, 9% vs 19, 3%; P=0, 211). Además, no se encontró ninguna diferencia entre los grupos en cuanto a la sensación de abultamiento vaginal (EAV, 7, 4 vs 6, 0 mm; P=0, 598), la distancia del POP desde el himen en el compartimento dominante del prolapso (‐1.8 vs –2, 0 cm; P=0, 556) y el descenso de la vejiga medido en ecografía (0, 5 vs 0, 8 cm; P=0, 058), del cuello uterino (‐1, 3 vs ‐1, 1 cm; P=0, 569) y de la ampolla rectal (0, 3 vs 0, 4 cm; P=0, 434). En todas las pacientes, en comparación con los hallazgos del examen inicial, la contracción muscular mejoró después de la cirugía, según se evaluó mediante la palpación (EOM, 2, 1 vs 2, 3; P=0, 007) y la ecografía (cambio en la DPA del hiato, 17, 5% vs 20, 1%; P=0, 001), y se redujo la sensación de abultamiento vaginal (EAV, 57.6 vs 6.7 mm; P<0.001). Además, en comparación con el examen de referencia, se redujeron la distancia del POP del himen en el compartimento dominante del prolapso (1, 9 vs –1, 9 cm; P<0.001) y el descenso de la vejiga medido en ecografía (1, 3 vs 0, 6 cm; P<0.001), del cuello uterino (0, 0 vs −1, 2 cm; P<0.001) y de la ampolla rectal (0, 9 vs 0, 4 cm; P=0.001). Conclusiones: No se encontró ningún efecto de los EMSP preoperatorios en la contracción de los MSP, los síntomas del POP o el prolapso anatómico después de la cirugía. En todas las pacientes, la contracción de los MSP y los síntomas del POP mejoraron en el seguimiento a los 6 meses, debido muy probablemente a la corrección anatómica del POP. Copyright © 2020 ISUOG. Published by John Wiley & Sons Ltd. 摘要: 术前骨盆底肌肉训练对术后骨盆底肌肉收缩以及有症状的和解剖性盆腔器官脱垂的影响:随机对照试验 目的: 在脱垂手术后六个月评估术前骨盆底肌肉训练(PFMT)对骨盆底肌肉(PFM)收缩、盆腔器官脱垂(POP)和解剖性 POP 的症状的影响，并评估术后 PFM 收缩、POP 症状和盆腔器官脱垂方面的总体变化。 方法: 这是一项随机对照试验，其中包括计划进行手术的 159 例患有有症状 POP(至少 2 级)的女性患者。参与者被随机分入干预组(包括从入组到手术的时期内每日进行 PFMT(n=81))或非干预组(对照组；n=78)。在入组时、手术当天和术后 6 个月，对参与者进行了检查。通过以下方法来评估 PFM 收缩:使用改良牛津量表(MOS；0‐5)来进行阴道触诊；经会阴超声(测量从静止到最大 PFM 收缩的提肌裂孔前后径(APD)的变化百分比)；阴道测压；以及表面肌电图(EMG)。在最大瓦氏动作下，测量距主要脱垂腔室中的处女膜的 POP 距离，以及前、中和后腔室中的器官脱垂。基于阴道膨出感而评估了 POP 症状。使用视觉模拟量表(VAS；0‐100 mm)对阴道膨出感进行分级。线性混合模型用于评估 PFMT 对结果变量的影响。 结果: 在随机分组的 159 名妇女中，有 151 名完成了研究(干预组有 75 名受试者完成研究，对照组有 76 名受试者完成研究)。平均手术等待时间为 22±9.7 周，平均在手术后 28±7.8 周进行随访。术后，干预组和对照组之间在通过阴道触诊(MOS，2.4 vs 2.2；P=0.101)、测压法(19.4 vs 19.7 cm H2 O；P=0.793)、表面 EMG(33.5 vs 33.1 mV；P=0.815)和超声检查(裂孔 APD 的变化，20.9% vs 19.3%；P=0.211)评估的 PFM 收缩方面没有差异。此外，两组之间在阴道膨出感(VAS，7.4 vs 6.0 mm；P=0.598)，从主要脱垂腔室的处女膜开始测量的 POP 距离(‐1.8 vs ‐2.0 cm；P=0.556)和超声检查的膀胱(0.5 vs 0.8 cm；P=0.058)、子宫颈(‐1.3 vs −1.1 cm; P=0.569)和直肠壶腹(0.3 vs 0.4 cm；P=0.434)脱垂方面没有差异。通过触诊(MOS，2.1 vs 2.3；P=0.007)和超声检查(裂孔 APD 的变化，17.5% vs 20.1%；P=0.001)进行评估，与初始检查时的结果相比，所有患者术后的肌肉收缩有所改善，并且阴道膨出感降低(VAS，57.6 vs 6.7 mm；P<0.001)。此外，与基线检查相比，从主要脱垂腔室的处女膜开始测量的 POP 距离(1.9 vs ‐1.9 cm；P<0.001)缩短，而且超声检查测得的膀胱(1.3 vs 0.6 cm；P<0.001)、子宫颈(0.0 vs ‐1.2 cm；P<0.001)和直肠壶腹(0.9 vs 0.4 cm；P=0.001)脱垂度降低。 版权 © 2020 ISUOG。由 John Wiley & Sons Ltd 出版。